β-catenin is a Potential Prognostic Biomarker in Uterine Sarcoma - Ying Cai MS; Yunjia Wang MS; Ling Yang MS; Yue Huang MS; Min-Jun Chen MS; Chi Zhang MS; Su-Han Jin MD, PhD; Benjamin Frey PhD; Udo S. Gaipl PhD; Hu Ma MD, PhD; Jian-Guo Zhou MD, PhD (Technology in Cancer Research & Treatment)
Introduction Uterine sarcoma (US) is an extremely rare and aggressive gynecologic malignancy with a poor overall survival (OS). The efficient prognostic biomarker is currently lacking. Methods Utilizing a Sweden microarray dataset from the Gene Expression Omnibus (GEO) (GSE119043, n = 50) and a clinical cohort (n = 31) retrospectively collected from Suining Central Hospital, we analyzed β-catenin expression profiles and corresponding clinicopathological characteristics. Immunohistochemistry (IHC) was used to assess β-catenin expression level. Survival analysis was used to assess the relationship between β-catenin expression and prognosis. Gene set enrichment analysis (GSEA) was performed to characterize the specific pathways involved in β-catenin expression. Results Immunohistochemistry indicated that β-catenin expression was significantly upregulated in US group compared to both the normal uterine smooth muscle (UNSM) and uterine leiomyoma (ULM) groups ( P  < .01). IHC also exhibited a significant difference in β-catenin expression levels in four pathological subtypes. Leiomyosarcoma (LMS) and high-grade endometrial stromal sarcoma (HG-ESS) suggested higher levels of β-catenin expression compared with adenosarcoma (AS) or low-grade endometrial stromal sarcoma (LG-ESS), but no statistically significant difference was found in box plot ( P  > .05). GSEA indicated that transcriptional dysregulation in cancer, Wnt, AMPK, MAPK, PI3K, p53, Ras, and TNF signaling pathway were positively enriched in β-catenin high-expression group. Though survival analysis showed that β-catenin expression level was not associated with survival, low-β-catenin expression group showed a longer median OS compared to high expression group (56.17 months VS 9.60 months) in Sweden microarray dataset. Similar results were also observed for progression-free survival (PFS) in clinical cohort (not reached VS 45.97 months in high-expression group). Tumor type, lymphadenectomy, family history of malignancy and tumor recurrence remained significant predictors of OS, while only tumor type, stage and tumor recurrence had prognostic significance for PFS. Age, tumor size, menopausal status, CA125, adjuvant chemotherapy, and adjuvant radiotherapy, were not associated with survival ( P  > .05). Conclusion β-catenin was highly expressed in uterine sarcoma and may be promising as a novel potential biomarker for diagnosis and prognosis.